1983
DOI: 10.1002/j.1552-4604.1983.tb02749.x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Metabolic Effects of Intravenous Terbutaline in Patients with Severe Heart Failure Due to Coronary Artery Disease

Abstract: Intravenous terbutaline, 0.3 mg/kg/min for 30 minutes followed by 0.15 mg/min for 60 minutes, was studied in nine patients with severe heart failure due to documented coronary artery disease. Hemodynamic and myocardial metabolic effects were measured during terbutaline infusion. Cardiac index and stroke index increased, whereas mean pulmonary artery wedge pressure and pulmonary vascular resistance decreased significantly. No significant alterations in aortic oxygen content, coronary sinus oxygen content, myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In a similar study, Saldías et al showed that the beta agonists intravenous isoproterenol and locally delivered (comparable to inhaled) terbutaline increased alveolar fluid resorption in rats with ventilator-associated lung injury (p Ͻ 0.001 compared to control animals) (38). McAuley et al found that in rats, locally delivered beta-2 agonists stimulated airspace fluid clearance in normal lungs and significantly reduced pulmonary edema in experimental acid-induced lung injury (30). Frank et al showed that in sheep with hydrostatic pulmonary edema, nebulized salmeterol resulted in a 60% increase in alveolar fluid clearance compared to placebo (40).…”
Section: Effect Of Acutely Delivered Beta-2 Agonists On Alveolar Fluimentioning
confidence: 92%
See 1 more Smart Citation
“…In a similar study, Saldías et al showed that the beta agonists intravenous isoproterenol and locally delivered (comparable to inhaled) terbutaline increased alveolar fluid resorption in rats with ventilator-associated lung injury (p Ͻ 0.001 compared to control animals) (38). McAuley et al found that in rats, locally delivered beta-2 agonists stimulated airspace fluid clearance in normal lungs and significantly reduced pulmonary edema in experimental acid-induced lung injury (30). Frank et al showed that in sheep with hydrostatic pulmonary edema, nebulized salmeterol resulted in a 60% increase in alveolar fluid clearance compared to placebo (40).…”
Section: Effect Of Acutely Delivered Beta-2 Agonists On Alveolar Fluimentioning
confidence: 92%
“…Fifteen studies with 230 patients reported on the occurrence of dysrhythmias (8 -10,13-15,18 -20,22-24,26,29). Six of these studies reported an increase in ventricular ectopy, with one reported episode of supraventricular tachycardia, and 4 patients with treatment-induced non-sustained ventricular tachycardia (8,20,22,24,29,30). No patient required treatment to terminate the dysrhythmia and all resolved with discontinuation of albuterol.…”
Section: Adverse Effects Of Acutely Administered Inhaled Beta-2 Agonimentioning
confidence: 95%
“…Several small studies in healthy subjects and patients with left ventricular dysfunction, heart failure, and cardiogenic shock have demonstrated improvements in cardiac index, dosedependent increases in heart rate, and reductions in total peripheral resistance with continuous intravenous infusions of terbutaline ranging from 0.15 to 0.45 µg/kg/min. [11][12][13][14][15][16] Another small study in patients (n = 10) who had undergone valve replacement surgery showed that intramuscular injections of terbutaline produced increases in cardiac index, heart rate, and reductions in total peripheral resistance. 17 In contrast, no effects on heart rate were seen in response to the administration of subcutaneous and inhaled terbutaline to patients with previous myocardial infarctions and heart failure, respectively.…”
Section: Discussionmentioning
confidence: 99%